Economic analysis of maize production in traditional and mechanized farming systems in Nilkantha Municipality, Dhading, Nepal - Shrestha, Subheksha; Shrestha, Promise; Chaulagai, Bibas; Khatri, Namuna; Bhattarai, Ranjan; Paudel, Dinesh (Archives of Agriculture and Environmental Science, 2025)
The purpose of this study was to evaluate the economic analysis as costs and profitability of maize production in traditional and mechanized farming systems. For this, a purposive random sampling of 101 maize farmers, comprising 30 using traditional methods and 71 employing mechanized systems was selected for structured household surveys. Cobb-Douglas production function, independent sample t-test, chi-square test, and descriptive statistics was performed using MS Excel and STATA software. Farmers under traditional and mechanized systems produced maize on average on 6.18 and 5.46 ropani, respectively. In mechanized systems, the mini tiller was the main tool used for the land preparation, while urea and farmyard manure (FYM) were the main suppliers of nutrients. Weeding was the most expensive operation in maize production. Traditional farming incurred higher costs for land preparation, planting, and plant protection. The net return per ropani was NRs. 1158.98 (8.47) for traditional farming and NRs. 1597.44 (11.67) for mechanized farming. The benefit-cost ratios were 1.42 for traditional and 1.57 for mechanized systems, respectively. Although the difference in returns per area between the two systems was not statistically significant, but mechanization effectively reduced production costs and enhanced profitability, representing a viable approach to improving maize farmers’ financial circumstances. Cobb-Douglas production function analysis revealed a coefficient sum of 0.756 for traditional systems and 1.248 for mechanized systems, indicating decreasing and increasing returns to scale, respectively. Therefore, adoption of mechanization for maize production is recommended for cost minimization and profit maximization in Dhading district of Nepal.